Promoting weight loss in people with schizophrenia: what do we still need to learn before implementing lifestyle interventions?. (February 2019) - Coventry, Peter; Peckham, Emily; Taylor, Jo
Abstract : Holt et al show that a lifestyle intervention did not reduce weight in people with schizophrenia. The STEPWISE trial casts a critical focus on the challenges of improving physical health in people with schizophrenia. The trial underpins efforts to maintain momentum in overcoming the unacceptable health inequalities in this population. Declaration of interest: None.